1981
DOI: 10.1017/s1742758400002228
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of sorghum shootfly reproduction

Abstract: This paper includes a description of the internal reproductive system of the female sorghum shootfly. Athcrigona soccata, as well as studies on egg maturation and survival, and effects of mating and/or presence of the male on egg maturation, fecundity and fertility. The number of ovarioles per female ranged from 20 to 47. A. soccata exhibits autogeny, but carbohydrate is essential for egg production and survival. Nutritional deficiency led to a high incidence of oocyte resorption. A mixture of baker's yeast an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1982
1982
1986
1986

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…In the shootfly, the first batch of eggs is ready for laying during the later part of the second day after adult emergence (Unnithan, 1982). No eggs are laid at night, however, and oviposition commences with a well-defined peak on the morning of the third day with another peak occurring in the late afternoon of the same day.…”
Section: Discussionmentioning
confidence: 99%
“…In the shootfly, the first batch of eggs is ready for laying during the later part of the second day after adult emergence (Unnithan, 1982). No eggs are laid at night, however, and oviposition commences with a well-defined peak on the morning of the third day with another peak occurring in the late afternoon of the same day.…”
Section: Discussionmentioning
confidence: 99%
“…These were (1) off-season shootflies (from off-season tillers in the farmers' fields), (2) shootflies whose larval and pupal stages were completed in CSH-1 seedlings subjected to dry conditions, and (3) those subjected to wet conditions in the greenhouse. These studies were conducted in the same way as described earlier (Unnithan, 1981).…”
Section: Reproductive Potential Of the Off-season Shootfliesmentioning
confidence: 99%
“…The largest average number of eggs reported for a group of flies was 238 and the largest number for one female was 440 (Meksongsee et al, 1980b). A female fly mates only once, subsequently producing fertile eggs throughout her lifetime (Unnithan, 1980). Adult flies feed on cereal aphid honeydew (Soto, 1972) and perhaps plant exudates.…”
Section: Description and Behaviormentioning
confidence: 99%
“…Adult flies feed on cereal aphid honeydew (Soto, 1972) and perhaps plant exudates. Unnithan (1980) demonstrated that including cereal aphid honeydew in the diet quickened oocyte maturation, but honeydew from the pea aphid was not suitable for survival. Shiang-Lin et al (1980) also stated that the presence of aphids seemed to increase shootfly attack.…”
Section: Description and Behaviormentioning
confidence: 99%
See 1 more Smart Citation